Teologi Liturgi Dan Ibadah Virtual - Dwi Kristantyo, Apolos (Sekolah Tinggi Teologi Sriwijaya, 2024)
Liturgy is not only about the arrangement of the service program, not only about the agenda of worship. But the service itself is a liturgy. Because of this, we know the terms Sunday worship liturgy, family worship liturgy, marriage confirmation and blessing liturgy, funeral liturgy and so on. What exactly do we understand by liturgical theology and virtual worship? Because churches have held virtual services and liturgy, which were not held before. And will virtual worship still be relevant when the pandemic has passed? Therefore, this article is intended to examine the theology of liturgy and virtual worship. Liturgical theology and virtual worship are actually theology and reflection, as well as Christian congregational activities that can be applied or practiced directly in certain situations, in this case during the Covid-19 pandemic. When the Covid-19 pandemic has passed, then virtual worship is possible is no longer needed. Because basically direct fellowship in places of worship or churches, where the congregation meets and shakes hands in person, is an essential need for humans as social creatures. However, it is still possible to hold virtual services because it is necessary for congregants who are sick and have permanent illnesses, so that congregants cannot come to worship at the house of worship directly and want to receive online worship services.